Using The Problem Based Learning Model With Youtube Media to Improve Student's Learning Interest - Ratna Utami Nur Ajizah; Khalis Zamrani Putra; Miftahudin (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2022)
Problem-based learning is often compared to conventional learning to reform educators' learning routines in the last ten years. According to the researcher, problem-based learning is proven to increase students' attention and interest. However, problem-based learning becomes ineffective if students are not interested in the problems to be solved. Therefore, it takes the help of learning media to stimulate students' interest in learning. Media that can be integrated in learning is YouTube. Based on these alternative media, YouTube was chosen to support the Problem Based Learning model. YouTube is a very appropriate medium to overcome the problems that exist in schools.